Evaluation of Assistive Technologies from the perspective of Usability, User Experience and Accessibility: a Systematic Mapping Study - de Godoi, Tatiany Xavier; Guerino, Guilherme Corredato; Valentim, Natasha Malveira C. (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2021)
Assistive Technologies (AT) are technologies that promote and extend the functional abilities of the users. Unfortunately, several technologies are abandoned by their users' difficulties, such as handling, high cognitive load, need for follow-up service, and device quality. To improve the quality of ATs and minimize their failures, evaluations of these ATs are performed. When an AT is evaluated, one should think of every user who can use it, thus making these ATs more accessible, more usable, and providing a good user experience (UX). However, several studies have investigated aspects of Usability, UX, and Accessibility separately. Therefore, it is required to characterize state of the art about AT evaluation related to these three software quality factors. This paper aims to show the results of a Systematic Mapping Study (SMS) on technologies that can be employed to evaluate the factors of Usability, User Experience (UX), and Accessibility to add more quality to AT. From 368 initial papers found in three research databases, 112 relevant papers were extracted based on the inclusion criteria. None of the studied initiatives evaluate the AT from the perspective of Usability, Accessibility, and UX together. Also, few evaluation instruments are tested with the public with which AT is directed. There are also few evaluation instruments for deaf users.